Single Cell and Population Activities in Cortical-like Systems - Bazsó, Fülöp; Kepecs, Ádám; Lengyel, Máte; Payrits, Szabolcs; Szalisznyó, Krisztina; Zalányi, Lászlo; Érdi, Peter (Reviews in the neurosciences, 1999)
Dynamics of single cells and large cell populations are the subject of investigation by using differently detailed models. Multicompartmental modeling techniques are used to systematically investigate the location-dependent effects of GABA-ergic inhibition on the firing patterns of hippocampal pyramidal cells. Appearance of stochastic resonance in a model of mitral and granule cells of the olfactory bulb is demonstrated by using a single-compartmental model approach. Spatial propagation of synchronized activities in hippocampal slices are studied by a model of large neural populations.